Assessment of the impact of the COVID-19 pandemic on the hospitality industry in Poland. Theoretical and empirical approach - Dahlke, Paweł; Orfin-Tomaszewska, Katarzyna; Sosnowski, Piotr (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The global COVID-19 pandemic has significantly affected the economy, including the functioning of the hospitality industry. The aim of the article is to analyse the impact of the SARS-CoV-2 virus pandemic on the functioning of Polish hotels, as well as to identify solutions used in the hospitality industry as part of reducing its negative effects. Through quantitative and qualitative research, the current situation of the hospitality industry in Poland was analysed and a survey was carried out among categorized hotel facilities using the CAWI method. The authors of the article collected and analysed selected solutions in the hospitality industry in the light of COVID-19. The results of the survey were also thoroughly analysed. The survey included issues related to the sanitary safety of facilities, the financial aspect of functioning in the legal restrictions caused by the pandemic, the effects of the pandemic on individual areas of hotel operations, or the assessment of the effectiveness of assistance offered to the hospitality industry by the state as part of anti-crisis shields. The obtained results confirmed the extremely difficult situation of hotels in Poland, insufficient state aid and difficulties that the hotels will face in the near future.